4th IET Clean Energy and Technology Conference (CEAT 2016) 2016
DOI: 10.1049/cp.2016.1300
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of P&O and modified incremental conductance algorithm in solar maximum power point tracking

Abstract: Photovoltaic (PV) system has been widely used as one of the renewable energy resources. Due to the non-linear I-V characteristic and changes of the external environment and load, the output power of the PV array varies according to different situation. Hence, the maximum power point (MPP) tracking technology is necessary to be implemented in order to track for the only MPP on the P-V curve to increase the energy harness from the PV array. In this study, two commonly used MPPT algorithm, perturb and observe and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The first continuously track voltage and current, in order to dynamically adjust the power operation point, without the need for any empirical information. Algorithms like perturb and observe (P&O), incremental conductance (IC), or hill climbing (HC) belongs to this category [47][48][49] and are characterized by high hardware, complexity, continuous functionality, and high efficiency, especially if the behavior of the energy source is unknown. Other MPPT techniques like fractional open-circuit voltage (FOCV) or fractional short-circuit current (FSCC) requires less complexity and measured data, without the need of continuously track the input voltage and/or current since they rely on a priori information about the source [50,51].…”
Section: Methodsmentioning
confidence: 99%
“…The first continuously track voltage and current, in order to dynamically adjust the power operation point, without the need for any empirical information. Algorithms like perturb and observe (P&O), incremental conductance (IC), or hill climbing (HC) belongs to this category [47][48][49] and are characterized by high hardware, complexity, continuous functionality, and high efficiency, especially if the behavior of the energy source is unknown. Other MPPT techniques like fractional open-circuit voltage (FOCV) or fractional short-circuit current (FSCC) requires less complexity and measured data, without the need of continuously track the input voltage and/or current since they rely on a priori information about the source [50,51].…”
Section: Methodsmentioning
confidence: 99%
“…This algorithm has been adopted by researchers to investigate the PV system's performance [37]- [40]. Also, it is chosen due to having some advantages, consisting of less computational procedure, ease of implementation, low complexity, and low power consumption [41]- [44]. Moreover, P&O is one of the most industry prevalent algorithms besides incremental conductance (INC) and constant voltage (CV) [45].…”
Section: Maximum Power Point Trackingmentioning
confidence: 99%
“…It is based on how current and duty cycle relate to one another. [10] The comparison analysis between modified MPPT algorithm and conventional P&O algorithm was done by [11,12] MPP algorithm and PI controller is used in this work and it had been observed that the steady-state and dynamic performance was quite satisfactory. Also the proposed system gave satisfactory results when operated under 30% of insolation levels.…”
Section: Figure 1 Circuit Diagram Of Sepic Convertermentioning
confidence: 99%